Interplay of enterprise social media and learning at work: a qualitative investigation. Issue 2 (13th May 2021) - Sharma, Anshu; Bhatnagar, Jyotsna; Jaiswal, Mahadeo; Thite, Mohan
Abstract : Purpose: The study aims to understand enterprise social media usage at work and explore its impact on employee outcomes, particularly learning behaviors. The scope of the paper is limited to organizationally facilitated enterprise social media (ESM) used internally for workplace communication and draws upon ESM affordances highlighted by the theory of communication visibility. Design/methodology/approach: The study used a qualitative research design based on Miles and Huberman framework (1994) as the research question was exploratory in nature. Thematic analysis was conducted using QSR-NVivo to arrive at the dominant themes and to understand their relationship between enterprise social media use at work. Each emergent theme was generated from the behavioral indicators labelled as nodes. Drawing on qualitative data, the study explored the lived-in experiences of employees using enterprise social media for workplace interactions. Findings: The thematic analysis using QSR-NVivo provided qualitative evidence for the phenomenon of enterprise social media use in the form of four emergent themes: patterns of enterprise social media usage by employees, employees' informal learning behaviors, employee social capital and organizational learning capability. Research limitations/implications: The study provides theoretical insights into the lived-in experiences of employees using ESM at work and unravel thematic behavioral impact on their learning, social capital and organizational learning capability. The findings of this study support recent research work on impact of ESM on knowledge sharing behaviors (see Sun et al., 2019) and other significant work on co-creation of knowledge (see Wagner et al., 2014). Thus, adding to the body of knowledge management literature. Practical implications: This study provides evidence for the role of enterprise social media in developing organizational learning capability by offering support and platform for employees' informal learning and building their social capital. Thus, organizations should leverage enterprise social media not only a social networking tool but more as a strategic learning resource. Hence, organizational leaders must encourage employees to be involved on such platforms in order to promote their informal learning. Also, this study captures the role of employee social capital in explaining the enterprise social media, informal learning and organizational learning capability relationship. This shows that enterprise social media can help employees to learn informally when they have good relationships. Hence, this study provides implications for both HR and IT managers and consultants who plan to implement technology for collaborative purposes, should not undermine the importance of building employee social capital. Only then can they utilize the potential of ESM as a learning tool. Last, this research may also influence the general attitude towards social media use at work and further impact the design and implementation of organizational social media policies. Originality/value: The paper is novel as the qualitative investigation offers deeper insights into the impact of ESM usage on employee and organizational learning behaviors. The paper draws on theoretical underpinnings to present useful linkages between emergent concepts and makes valuable contribution to the literature on enterprise social media use and learning at work.